Perceptual congruence and change : non-urban communities and land-use planning - Lemon, M. (Cranfield University, 1991)
The planning and management of change has tended to be directed towards the achievement of end states. Adaptive procedures are generally undertaken when it is felt that these end states will not be reached and intervention is necessary. This intervention is usually determined by the technical and organizational criteria of the management system. This thesis argues, using the land-use planning system as a central example, that such an approach to change management fails to acknowledge the diversity of the process. Two points are considered to be fundamental to this argument. Firstly, that diversity is the generator of change, and not merely an inconvenient constraint upon its management Secondly, change follows multi-dimensional pathways (through time, across space, and between themes), that do not conform to technical, linear. management criteria. Failure to recognise these points inevitably hinders the ability of management systems to adapt to the uncertainty of the environment for which they have assumed responsibility. One measure of this failure is the mis-match between the agenda set by the managers of change, and that which is desired by the consumers of the process. The thesis supports the need for integrated management systems that are cognizant of, and driven by, the variety which is identified within the consumer agenda. The field work for the study considers ways of identifying the nature and extent of this variety. It will be argued that individuals interpret, negotiate, and effect change interactively with the wider social system. This interaction combines with the social and physical environments encountered by individuals in their daily lives, to define a 'sense of place'. A multi-method approach is developed which uses the demographic attributes of the . study village as bench marks that will allow comparison with other localities, and place it on an urban - rural continuum. This quantitative data also provides a means by which the variety of qualitative data can be assessed, and upon which provisional classifications about how particular groupings respond to change can be based. An interview and questionnaire instrument will be introduced. This will enable respondents to construct their own cognitive pathways of how changes which are pertinent to the local environment have evolve~. These pathways are then compared with the criteria Identified In land-use planning documentation, and the level of congruence between the two examined.